Atopic Dermatitis and Water: Is There an Optimum Water Intake Level for Improving Atopic Skin? - Nikolaos Douladiris; Efstratios Vakirlis; Emilia Vassilopoulou (MDPI AG, 2023)
Water is a vital nutrient with innumerable functions for every living cell. The functions of human skin include protection against dehydration of the body. Atopic dermatitis (AD) is a chronic pruritic inflammatory skin disease that presents with dry skin, erythematous and eczematous lesions, and lichenification. This paper discusses the question of whether extra water intake in children with AD affects skin hydration and the skin barrier function. Among the methods used to treat dry skin, topical leave-on products are the first-line treatment, intended to improve hydration and the skin barrier function. The effectiveness of adequate water intake as a measure to treat dry skin is still under debate. Normal skin hydration increases with dietary water intake, particularly in those with prior lower water consumption. Skin dryness in AD is instrumental to the itch and inflammation cycle, contributing to barrier impairment and aggravating disease severity and flares. Certain emollients provide significant hydration to AD skin, with relief of dryness and reduction in barrier impairment, disease severity, and flares. Further investigations are needed to evaluate the optimum water intake levels in children with AD, as important questions remain unanswered, namely, does oral hydration provide relief of skin dryness and reduce barrier impairment, disease severity, and flares; is there any additional benefit from using mineral or thermal spring water; or is there a need to specifically study the fluid/water intake in children with AD and food allergy (FA) restrictions?